Živimo v času sodniškega prava - Pavliha, Marko (Pravnik, 2023)
The monograph Judicial Law is the result of a symposium at the Slovenian Academy of Sciences and Arts and the University of Ljubljana Faculty of Law, which took place in the beginning of 2023. The book was edited by academician Professor Marijan Pavčnik and Assistant Professor Aleš Novak, and in addition to them, eight other prominent authors and two female authors participated: Maja Brkan, Tilen Štajnpihler Božič, Samo Bardutzky, Matej Accetto, Aleš Galič, Miro Cerar, Janez Kranjc, Tomaž Pavčnik, Primož Gorkič and Nina Betetto. In addition to classic scientific instruments, the book contains eleven comprehensive chapters in which the authors deal in depth with the concept and occurrence of judicial law, the Court of the EU as a (co)creator of European law, reference to foreign judicial law in Slovenian constitutional review, strategic litigation and adjudication, guarantees regarding uniform judicial practice within the framework of the right to a fair trial, the judge’s (un)binding to secondary general acts, the praetor’s creation of new law in the procedure, civil law institutes and the constitution as a source of judicial law, courts as (co)creators of the rules of criminal procedural law and soft judicial law.
Keywords: pravna ureditev; sodišča; sodna praksa; sodniki; sodniško pravo; sodstvo; Ustavno sodišče; zakonodaja